Impacto do uso do solo e altitude sob a dinâmica do carbono e fósforo no bioma Mata Atlântica - Ferreira, Anna Carolyna Fernandes (2017)
The study of the dynamics of soil organic matter (SOM) and nutrients affected by different soil uses is essential for understanding the effects of agricultural activities on the environment. The objective of this study was to evaluate stock carbon (EC), n